Analytical study of the sayings of jurists regarding zakat on jewelry - Shafiq, Muhammad; Al Hassani, Muhammad Nawaz (Al-Irfan, 2021)
Zakat is one that of the basic and important pillars of Islam and is the part of economic system of Islam which is why Jurists, Scholars, Commentators, and experts have discussed in detail all aspects of it. The issues of Zakat which have been discussed in detail by these gentlemen Zakat on Jewellery is one of these problems. As with other issues of Zakat there is a difference of opinion between the jurists of Ahnaf and the view of Ibn-e-Hazm is that Zakat is obligatory on gold and silver jewellery while some of the companions, Jurists of Malkiya, Shuafa and Hanaballah’s view are that Zakat is not obligatory on gold and silver jewellery. The following is a link to a series of articles in stance of Islamic Scholars regarding the obligations of Zakat and non-compulsion on gold and silver jewellery will be presented, and a critical review of the arguments presented by them later. Taking into account the Rajah stand will be presented as a discussion.